Reproducibility and robustness of motor cortical stimulation to assess muscle relaxation kinetics - Molenaar, Joery P.; Zandvoort, Elianne; Engelen, Baziel G.; Voermans, Nicol C.; Doorduin, Jonne (Physiological reports, 2022)
Transcranial magnetic stimulation (TMS) of the motor cortex can be used during a voluntary contraction to inhibit corticospinal drive to the muscle and consequently induce involuntary muscle relaxation. Our aim was to evaluate the reproducibility and the effect of varying experimental conditions (robustness) of TMS‐induced muscle relaxation. Relaxation of deep finger flexors was assessed in 10 healthy subjects (5 M, 5 F) using handgrip dynamometry with normalized peak relaxation rate as main outcome measure, that is, peak relaxation rate divided by (voluntary plus TMS‐evoked)force prior to relaxation. Both interday and interrater reliability of relaxation rate were high with intraclass correlation coefficient of 0.88 and 0.92 and coefficient of variation of 3.8 and 3.7%, respectively. Target forces of 37.5% of maximal voluntary force or higher resulted in similar relaxation rate. From 50% of maximal stimulator output and higher relaxation rate remained the same. Only the most lateral position (>2 cm from the vertex) rendered lower relaxation rate (mean ± SD: 11.1 ± 3.0 s−1, 95% CI: 9.0–13.3 s−1) compared to stimulation at the vertex (12.8 ± 1.89 s−1, 95% CI: 11.6–14.1 s−1). Within the range of baseline skin temperatures, an average change of 0.5 ± 0.2 s−1 in normalized peak relaxation rate was measured per 1°C change in skin temperature. In conclusion, interday and interrater reproducibility and reliability of TMS‐induced muscle relaxation of the finger flexors were high. Furthermore, this technique is robust with limited effect of target force, stimulation intensity, and coil position. Muscle relaxation is strongly affected by skin temperature; however, this effect is marginal within the normal skin temperature range. We deem this technique well suited for clinical and scientific assessment of muscle relaxation. Transcranial magnetic stimulation (TMS) can be used to assess muscle relaxation during a voluntary contraction by abruptly halting neural drive to the muscle. Our results show that this technique has high interday and interrater reproducibility and reliability. Furthermore, generated results are robust with limited effect of target force, stimulation intensity, coil position, and skin temperature on relaxation rate. TMS‐induced muscle relaxation appears well suited for clinical and scientific assessment of muscle relaxation rate.